سي أمحمد بن رحال ودوره في الدفاع عن قضايا الجزائريين - بودن، غانم (جامعة حسيبة بن بوعلي بالشلف, 2017)
عملت السياسة الاستعمارية فى الجزائر منذ الاحتلال على القضاء على كل مقومات الشعب الجزائرى المادية والمعنوية، فألحقت الجزائر بفرنسا وصادرت الأراضي الزراعية وأملاك الوقف التي كانت تضمن التعليم للجزائريين خدمة لسياسة التجهيل الاستعمارية لضمان خضوع الشعب، ووأد كل حركة وعي محتملة مستقبلا تهدد الوجود الفرنسي، ولكن رغم هذه السياسة إلا أن الجزائريين تمسكوا بالتعليم العربي تحت الظروف القاسية ، واستفادوا من التعليم الفرنسي الذي فرض عليهم بجعله وسيلة لإثبات الذات وتحقيق مكاسب مختلفة ٠ وقد شهدت نهاية القرن التاسع عشر ميلادي ظهور الفكر المطلبي الذي جسدته النخبة الجزائرية المثقفة التى حققت مكانة علمية واجتماعية محترمة، استطاعت بفضلها أن تنقل اهتمامات مواطنيها وانشغالاتهم للسلطات الاستمارية للنظر فيها وإيجاد حلول لها فى المجال الدينى، والتقافي والاقتصاد، ومن هذه الوجوه التي مثلت الرأي العام الجزائري لمدة أربعين سنة أمام الادارة الاستعمارية سي امحمد بن رحال الندرومي (1858-1928) الذي يعتبر من أبرز وجوه النخبة المحافظة غربي الجزائر. سجل حضوره في كل المناسبات ورافع في مختلف المنابر الفرنسية لإيصال صوت الجزائريين المنادين بالتخفيف من وطأة السياسة الاستعمارية في بعض المجالات كالتعليم والقضاء الإسلامي والتجنيد، وقضى الفترة الزمنية(1886-1925) كمحاور للنظام الاستعماري لصالح مواطنيه مؤسسا بذلك لأسلوب المقاومة الحوار لتحقيق المطالب، استغل كل فرصة داخل الجزائر وخارجها لإسماع صوت الجزائريين، ورد المظالم عنهم. إن دراسة سير النخبة الجزائرية في التاريخ المعاصر مهمة لأن نشاطها يشكل مرآة عاكسة لخصائص عصرها; ويبرز دورها فيه إيجابا وسلبا، وفى هذا الإطار تأتى هذه الدراسة التى تحاول إبراز نشاط سى امحمد بن رحال فى الدفا۶ عن قضايا الجرائريين الاجتماعية والثقافية والسياسية.
One of the French colonial policies in Algeria was to uproot every moral or material Algerian value. It confiscated agricultural lands and moratorium properties, which were meant to ensure education for Algerians aiming at subjugating the people and killing every single potential future conscious movement that may represent a threat to the French presence in Algeria. However, Algerians clung to their education under harsh circumstances and benefited from the French education imposed on them using it as a means of different gains and self-assertion. The end of the nineteenth century witnessed the emergence of the demand thinking embodied in the Algerian elite. They realized respectable, social, and scientific status due to which they transmitted the citizens’ concerns to the colonial authorities to be discussed and settled religiously, culturally, and economically. Among the elite who represented the Algerian public opinion was si M'hamed Rahal (1858-1928). He was one of the most prominent conservative elite in western Algeria. He attended many occasions and spoke from different French platforms to make the voice of the Algerian advocates of colonial policy alleviation in education, Islamic judiciary, and recruitment heard nationally and internationally. He spent the period (1886-1925) as an interlocutor of the colonial system for his citizens, establishing the resistance dialogue to achieve their demands. The study of the functioning of the Algerian elite in contemporary history is important because its activity is a mirror reflecting the characteristics of the age, and highlights the role of the positively and negatively. In this context comes the study, which is trying to highlight the activity of si M'hamed Rahal in the defense of the social, cultural and political Algerians issues. The study of the Algerian elite in the contemporary history is of a paramount importance as its activity represents a reflecting mirror of its age features. It demonstrates its role positively and negatively. Therefore, this paper aims at presenting the work of si M'hamed Rahal in shielding wwthe Algerian social, cultural, and political issues
Keywords: الندرومى، سي أمحمد بن رحال، ت. 1928 م. -- الاستعمار الفرنسى -- السياسة الاستعمارية -- مدينة ندرومة بتلمسا -- الجزائر